Multiplex PCR Assay for the Identification of Four Species of the Anopheles Leucosphyrus Sub-Group in Malaysia. Insects 2022, 13, 195 - Sandthya, Pramasivan; Jonathan Wee Kent, Liew; Nantha Kuma, Jeyaprakasam; Van, Lun Low; Romano, Ngui; Indra, Vythilingam (MDPI, 2022)
The Leucosphyrus Group of mosquitoes are the major simian malaria vectors in Malaysia. Accurate species identification is required to help in curbing the spread of simian malaria. The aim of the study is to provide an accurate molecular method for identifying the four important Anopheles vector species found in Malaysia. Mosquito specimens were collected from various localities in Ma- laysia, where simian malaria cases were reported. DNA from 122 mosquito specimens was tested to develop a multiplex polymerase chain reaction (PCR) assay. The specificity of this assay was tested against other mosquito species. Molecular identification of the species was further confirmed by analysing the internal transcribed spacer 2 (ITS2) DNA region of the specimens. Anopheles bala- bacensis and An. latens showed two distinct clades in the phylogenetic tree. The multiplex PCR assay was developed based on the ITS2 region for the identification of Anopheles introlatus (298–299 bp), Anopheles latens (197–198 bp), Anopheles cracens (421–426 bp), and Anopheles balabacensis (224–228 bp). This method will be useful to accurately identify the major Anopheles Leucosphyrus Group species in Malaysia, which are difficult to identify morphologically, to determine the correct vector as well as its geographical distribution